2000
DOI: 10.1023/a:1008382706068
|View full text |Cite
|
Sign up to set email alerts
|

A pilot trial assessing the efficacy of paroxetine hydrochloride (Paxil®) in controlling hot flashes in breast cancer survivors

Abstract: Paroxetine hydrochloride is a promising new treatment for hot flashes in breast cancer survivors, and warrants further evaluation in a double-blind randomized placebo-controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(121 citation statements)
references
References 15 publications
3
111
0
7
Order By: Relevance
“…Thus, we choose paroxetine for this study. As it has reported that low dose (10-20 mg/day) of paroxetine is effective and safe for HF patients with breast cancer survivor, 19 we propose that 10 mg/day is reasonable initial dosages. In this study, efficacy of low dose of paroxetine (10 mg/day) were observed at first week in three patients (3/10: 30%), second week in three patients (3/10: 30%), third week in two patients (2/10: 20%) and fourth week in two patients (2/10 20%), so the progress of HF symptoms should be observed for at least 4 weeks and if symptoms do not improve within a month, the dosage can be increased.…”
Section: Patientmentioning
confidence: 84%
“…Thus, we choose paroxetine for this study. As it has reported that low dose (10-20 mg/day) of paroxetine is effective and safe for HF patients with breast cancer survivor, 19 we propose that 10 mg/day is reasonable initial dosages. In this study, efficacy of low dose of paroxetine (10 mg/day) were observed at first week in three patients (3/10: 30%), second week in three patients (3/10: 30%), third week in two patients (2/10: 20%) and fourth week in two patients (2/10 20%), so the progress of HF symptoms should be observed for at least 4 weeks and if symptoms do not improve within a month, the dosage can be increased.…”
Section: Patientmentioning
confidence: 84%
“…Bu ilaç ile yapılmış çalışmalarda özellikle ruhsal bazı semptomları düzelttiği gös-terilse de özellikle ileri evra kanser hastalarında kullanımı yan etkiler nedeniyle zordur. [48,49] Trazodon ise atipik tetrasiklik antidepresandır, hem presinaptik hem de postsinaptik seratonin reseptörlerini bloke eder. [50] Uyku probemleri yanında depresyon, ağrı, deliryum semptomunun palyasyonunda da kullanılmaktadır.…”
Section: Tablounclassified
“…[54,55] Terminal dönem olmayan kanser hastalarında yapılan iki randomize kontrollü olmayan çalışma-da mirtazapin ve paroksetin özellikle uyku sorunları için çalışılmıştır. [56,57] Her iki çalışmada da yan etkiler nedeniyle oldukça fazla oranlarda ilacı bı-rakma oranları gözlenmiştir. Direk uyku sorunları-na hedeflemeyen yorgunluk, depresyon gibi farklı fakat ilişkili semptomları hedefleyen çalışmalar da literatürde bulunmaktadır.…”
Section: Kemoterapiunclassified
“…This led to the conduct of pilot trials evaluating venlafaxine (a serotonin/norepinephrine reuptake inhibitor [SNRI]) and paroxetine (a selective serotonin reuptake inhibitor [SSRI]). Published results from the pilot studies of venlafaxine and paroxetine were promising, 23,24 suggesting the drugs were efficacious and well tolerated. Subsequently, a placebo-controlled, double-blind, dosefinding randomized trial was conducted to evaluate venlafaxine in 191 women with hot flashes who either were survivors of breast cancer or who did not want to take HT for fear of breast cancer.…”
Section: Newer Antidepressantsmentioning
confidence: 99%